Evolutionary origins and functions of the carotenoid biosynthetic pathway in marine diatoms - Coesel, Sacha (2014)
Carotenoids are produced by all photosynthetic organisms, where they play essential roles in light harvesting and photoprotection. The carotenoid biosynthetic pathway of diatoms is largely unstudied, but is of particular interest because these organisms have a very different evolutionary history with respect to the Plantae and are thought to be derived from an ancient secondary endosymbiosis between heterotrophic and autotrophic eukaryotes. Furthermore, diatoms have an additional xanthophyll-based cycle for dissipating excess light energy with respect to green algae and higher plants. To explore the origins and functions of the carotenoid pathway in diatoms we searched for genes encoding pathway components in the recently completed genome sequences of two marine diatoms. Consistent with the supplemental xanthophyll cycle in diatoms, we found more copies of the genes encoding violaxanthin de-epoxidase (VDE) and zeaxanthin epoxidase (ZEP) enzymes compared with other photosynthetic eukaryotes. However, the similarity of these enzymes with those of higher plants indicates that they had very probably diversified before the secondary endosymbiosis had occurred, implying that VDE and ZEP represent early eukaryotic innovations in the Plantae. Consequently, the diatom chromist lineage likely obtained all paralogues of ZEP and VDE genes during the process of secondary endosymbiosis by gene transfer from the nucleus of the algal endosymbiont to the host nucleus. Furthermore, the presence of a ZEP gene in Tetrahymena thermophila provides the first evidence for a secondary plastid gene encoded in a heterotrophic ciliate, providing support for the chromalveolate hypothesis. Protein domain structures and expression analyses in the pennate diatom Phaeodactylum tricornutum indicate diverse roles for the different ZEP and VDE isoforms and demonstrate that they are differentially regulated by light. These studies therefore reveal the ancient origins of several components of the carotenoid biosynthesis pathway in photosynthetic eukaryotes and provide information about how they have diversified and acquired new functions in the diatoms.